International Approaches to the Analysis of the Phenomena of BRICS Transregionalism - Ilya V. Ilyin (Sravnitelʹnaâ Politika, 2017)
The article analyzes the essence, location, status, and role of the informal BRICS grouping. The authors examine and compare the different points of view on this phenomenon and believe that the comparative and economical approaches that dominate in the contemporary studies of the BRICS are unproductive. While member countries of the Association are experiencing economic slowdown or recession, BRICS is gradually becoming a political phenomenon of the global world.BRICS is considered the center of an impact of the regional leaders on three continents. A specifi c model of communication of the member countries of the BRICS and their partners is polylogue as one of the methods to solve the problem of equitable participation of all countries of the global world in the process of global governance. In the geopolitical framework of the BRICS and their partners, it is the formation of an extra-American zone of interaction, which will gradually evolve into a Global nonWestern project..